2021
DOI: 10.3390/v13071207
|View full text |Cite
|
Sign up to set email alerts
|

HDV-Like Viruses

Abstract: Hepatitis delta virus (HDV) is a defective human virus that lacks the ability to produce its own envelope proteins and is thus dependent on the presence of a helper virus, which provides its surface proteins to produce infectious particles. Hepatitis B virus (HBV) was so far thought to be the only helper virus described to be associated with HDV. However, recent studies showed that divergent HDV-like viruses could be detected in fishes, birds, amphibians, and invertebrates, without evidence of any HBV-like age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Our findings may explain the long-term HDV persistence in patients (>1 year) with liver transplantation and anti-HBsAg therapy, 9,10 and in HDV mono-infected mice (>6 weeks) with transplanted PHHs. 11 Moreover, a number of HDV-like agents were discovered recently from vertebrates and invertebrates (reviewed in 22 ). Most of these agents are not associated with hepadnaviruses and do not encode L-HDAg homologs with prenylation moieties.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings may explain the long-term HDV persistence in patients (>1 year) with liver transplantation and anti-HBsAg therapy, 9,10 and in HDV mono-infected mice (>6 weeks) with transplanted PHHs. 11 Moreover, a number of HDV-like agents were discovered recently from vertebrates and invertebrates (reviewed in 22 ). Most of these agents are not associated with hepadnaviruses and do not encode L-HDAg homologs with prenylation moieties.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 ] This strongly indicates that HDV has a much longer evolutionary history than previously anticipated, although the origin of HDV remains uncertain. [ 19 , 20 ]…”
Section: Hdv Virologymentioning
confidence: 99%
“…Recently, more HDV-like viruses (deltaviruses) have been discovered in a diverse range of hosts, including birds, [13] snakes, [14] rodents, [15] white-tailed deer, [16] Eastern woodchucks, [17] fish, amphibians, and even invertebrates [18] . This strongly indicates that HDV has a much longer evolutionary history than previously anticipated, although the origin of HDV remains uncertain [19,20] …”
Section: Hdv Virologymentioning
confidence: 99%
See 1 more Smart Citation
“…Metatranscriptomic studies revealed more deltaviruses in common vampire bats, a lesser dog-like bat, whitetailed deer, eastern woodchuck, passerine birds, zebra finch, lantern fish, and amboli leaping frogs [20][21][22]. The recent findings have sparked deltavirus research and raised questions about the evolutionary origin of deltaviruses [23][24][25]. The identification of deltaviruses across several taxa led to the establishment of a new realm, Ribozyviria, with family Kolmioviridae including eight genera [26,27].…”
Section: Introductionmentioning
confidence: 99%